Rhapsodic Readings: The Ion and Literary Knowledge - Moyes, Craig (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
Within the context of current debates on the institutional status of literature, this paper discusses the problem of literary knowledge through a detailed reading of Plato's Ion. It argues further that the structure of the negative response that Socrates offers to the rhapsode is curiously repeated by two modern apologists for literature, Sainte-Beuve et Eliot.